2012
DOI: 10.1111/j.1439-0396.2012.01328.x
|View full text |Cite
|
Sign up to set email alerts
|

Spirulina as a livestock supplement and animal feed

Abstract: Summary Spirulina (Athrospira sp.) is an edible microalga and a highly nutritious potential feed resource for many agriculturally important animal species. Research findings have associated Spirulina to improvements in animal growth, fertility, aesthetic and nutritional product quality. Spirulina intake has also been linked to an improvement in animal health and welfare. Its influence over animal development stems from its nutritive and protein‐rich composition, thus leading to an increased commercial producti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
139
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(146 citation statements)
references
References 48 publications
4
139
0
3
Order By: Relevance
“…A number of protein meals are commercially available but their cost generally prohibits widespread use. Potential sources of a novel high protein supplement available at low cost could include algal biodiesel residue (Bryant et al, 2012) or on-farm algal protein production (Holman and Malau-Aduli, 2013). The simulated liveweight gains found in this study assuming a cheap algal protein source was available are broadly consistent with experimental data for similar quality protein meals such as cottonseed meal (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…A number of protein meals are commercially available but their cost generally prohibits widespread use. Potential sources of a novel high protein supplement available at low cost could include algal biodiesel residue (Bryant et al, 2012) or on-farm algal protein production (Holman and Malau-Aduli, 2013). The simulated liveweight gains found in this study assuming a cheap algal protein source was available are broadly consistent with experimental data for similar quality protein meals such as cottonseed meal (e.g.…”
Section: Discussionsupporting
confidence: 74%
“…In their review, Farag et al (2016) pointed out that the antimicrobial and immunomodulatory (and anti-inflammatory) capacities as well as antioxidant potential seemed to be responsible for the healthpromoting effect of S. platensis on poultry. As well as growth and health performances, treatment with S. platensis was reported to increase carcass percentage and ready-to-cook yields of broiler chicks in the studies of Raju et al (2004), Kaoud (2012) and Holman & Malau-Aduli (2013). Moreover, Bonos et al (2016) showed that Spirulina supplementation (5 g/kg) was capable of improving the meat quality of broiler, that is, increasing the contents of eicosapentaenoic acid (EPA), docosapentaenoic acid (DPA) and docosahexaenoic acid (DHA) in the thigh muscles of broiler chicks.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with antibiotics and other broiler feed ingredients, S. platensis is more expensive (Holman & Malau-Aduli, 2013). Apart from its benefits, the application of Spirulina as the replacement for in-feed antibiotics in broiler production therefore seems impractical, especially when used throughout the rearing period.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of cultural and religious restraints to poultry meat consumption is also important (Cavani et al, 2010;Petracci et al, 2013). The inclusion of spirulina in broiler nutrition, besides having possible favourable effects on health and performance (Ravi et al, 2010;Kharde et al, 2012;Holman & Malau-Aduli, 2013;Shanmugapriya & Saravana Babu, 2014), might be a simple and convenient strategy to introduce its bioactive compounds into the meat and produce functional products according to consumer demand for healthy natural foodstuffs (Jimenez-Colmenero et al, 2001).…”
Section: Introductionmentioning
confidence: 99%